Flood hazard assessment and management of fetch-limited coastal environments - Carrasco, Ana Rita (2017)
Flooding is a significant environmental threat that can cause loss of human life, damage to infrastructure, disruption to economic activity, and decline in ecological resources in coastal areas. This paper presents a framework for assessing the potential implications of floods in fetch-limited coastal environments (with no significant wave setup), focused on hazard mapping and risk analysis. Hazard maps are based on defined return periods and risk estimates are determined by computing the extent of affected occupied and ecological areas lying below water levels associated with the return periods. For management purposes, this study chooses the adaptive management approach as the most feasible to improve local economies and mitigate the loss of natural areas, and identifies/recommends specific types of occupation and activity for each flood hazard zone. The proposed framework was applied to a low-energy fetch-limited beach, Ancão Peninsula backbarrier, located in the Ria Formosa barrier system (southern Portugal). Inundation levels predicted for 1-, 10-, and 100-year return periods were 2.02 m, 2.39 m, and 2.84 m above MSL (mean sea level), respectively. On this basis, flood impacts were found to be important in occupied areas, generating physical damage to residences and infrastructure. Ecological impacts of floods affected sub-aerial species inhabiting dunes. Several management options deriving from the framework’s application were recommended for the Ancão Peninsula.